PERANAN PEMERINTAH INDONESIA DALAM MENANGANI PENGUNGSI ROHINGYA DI ACEH TAHUN 2012-2015 - Rianti Nur Istiqomah (HI 15 UMY 409, 2015)
*409 The case of Rohingya have been started since a long time ago. These case become very large when the increasing number of asylum seekers who are scattered all over the world, including Indonesia. Until now, Indonesia did not have regulation to deal with So far, Indonesia has not specific regulations to deal with the refugee problem. So there is no clear law in Indonesia to deal with refugees. Regulation of refugee problems in international law stipulated in the Geneva Convention of 1951 and Protocol of 1967 relating to refugees, so that the regulation of refugee problems submitted to UNHCR. Efforts to do Indonesia is limited to humanitarian aid to be a facilitator. Provide assistance which Indonesia is a temporary shelter, food, clothing, and shelter. Indonesia to allow the arrival of asylum seekers to Indonesia, but Indonesia does not have an obligation to provide protection according to UNHCR standards because Indonesia has not ratified the refugee convention in 1951 and 1967.The results showed that Indonesia took the decision to help the Rohingya in order to uphold the 1945 Constitution and Pancasila chapter 2. The focus of this study discussing about the role of the Indonesian government in dealing with the Rohingya refugees in Aceh. By using a qualitative approach, emphasis on content analysis methods. Framework in this study using decision making theory and the concept of national interest. This study uses qualitative methodology because the data are taken from book, journar and websites. Keywords: Indonesian Government, Refugees, Rohingya